Hypothyroidism and early pregnancy loss: an overview - Verma, Puja; Roy, Dipti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Thyroid disorders are associated with adverse pregnancy outcomes and can lead to spontaneous miscarriages. Methods: One hundred and four women with early pregnancy loss were enrolled in this study and thyroid profile was done. Thyroid status of women was established on the basis of standard cut-off levels. Prevalence of hypothyroidism (both overt and subclinical) was calculated. Results: The mean TSH level was 2.3±1.3 μIU/l. Twenty two women had increased TSH level (>2.5 μIU/l) accounting to 21.15% of total women and rest 78.84% women were euthyroid. 15.38% of women presenting with early pregnancy loss were overt hypothyroid and 5.76% of women had subclinical hypothyroidism. The mean TSH level in hypothyroid group was 4.9±2.1. Conclusions: Hypothyroidism if untreated can lead to first trimester abortions. All pregnant women should be screened for thyroid disorders in their first visit and treatment should be started at the earliest.